2004
DOI: 10.1146/annurev.phyto.42.040803.140329
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approaches for Detection of Plant Pathogenic Bacteria and Diagnosis of Bacterial Diseases

Abstract: Disease diagnosis is based on a number of factors, including laboratory tests for pathogen identification. Rapid development of genomic techniques for characterization of bacteria over the past decade has greatly simplified and improved pathogen detection and identification, but DNA-based methods have not yet entirely replaced traditional culture and phenotypic tests in the plant industry. The first section of this review focuses on rapid immunodiagnostic and DNA-based detection methods for known bacterial pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 123 publications
2
137
0
5
Order By: Relevance
“…These quantification methods significantly extrapolate the number of viable cells in mixed populations (Nocker and Camper 2006). Other methods for determination of viable cells such as those utilising RNA-based diagnostics are expensive and time-consuming (Alvarez 2004;Norton and Batt 1999). EMA allows selective amplification of DNA by QPCR from only viable and not dead cells, which substantially increases the utility of PCR for rapidly determining and quantifying the presence of targeted viable microorganisms in environmental samples without enrichment (Rudi et al 2005).…”
Section: Dynamic Development Of Las Concentration In Plantamentioning
confidence: 99%
See 1 more Smart Citation
“…These quantification methods significantly extrapolate the number of viable cells in mixed populations (Nocker and Camper 2006). Other methods for determination of viable cells such as those utilising RNA-based diagnostics are expensive and time-consuming (Alvarez 2004;Norton and Batt 1999). EMA allows selective amplification of DNA by QPCR from only viable and not dead cells, which substantially increases the utility of PCR for rapidly determining and quantifying the presence of targeted viable microorganisms in environmental samples without enrichment (Rudi et al 2005).…”
Section: Dynamic Development Of Las Concentration In Plantamentioning
confidence: 99%
“…Quantitative assays are useful for determining the virulence mechanism(s) of pathogens, infection ability of insect vectors, and development of efficient management strategies (Alvarez 2004;Bach et al 2002). Since the efforts to isolate Las in pure culture have been unsuccessful, accurate quantification remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“…However, boiling the bacteria samples could improve the sensitivity of detection. Several previous reports have mention that using extraction buffer containing EDTA and lysozyme to removed cell surface component could improve the sensitivity of ELISA detection (Jones et al, 1997, Alvarez, 2004. However, EDTA was not used in this study but the sensitivity of detection was still high.…”
Section: Bacteria Isolation and Pathogenicity Testmentioning
confidence: 86%
“…Many studies reported that, the ELISA sensitivity 10 5~ 10 6 CFU/mL is sufficient for identification of bacteria pathogens from symptomatic plants and colonies on selective media (Jin et al, 2001;Alvarez, 2004;de Leon et al, 2008;Kokoskova and Mraz, 2008). However, boiling the bacteria samples could improve the sensitivity of detection.…”
Section: Bacteria Isolation and Pathogenicity Testmentioning
confidence: 99%
“…Antibodies are commercially available for use in immunofluorescence and ELISA (Jones et al, 1997;Alvarez, 2004); however, published data on their specificity across X. euvesicatoria, X. gardneri, X. perforans and X. vesicatoria are not reported. Some monoclonal antibodies appear to be species-specific (Bouzar et al, 1994a).…”
Section: Serological Methodsmentioning
confidence: 99%